Sustainable development indicators in ecological economics - Lawn, Philip A.; Edward Elgar Publishing (Cheltenham, U.K. ; Northampton, Mass : Edward Elgar, 2006)
Since the late 1980s and early 1990s, national governments have introduced a range of policy measures designed to steer their economies along a more sustainable path. Yet how are we to know how successful these have been? This significant new book discusses the ways in which sustainable development indicators can be improved in order to both assess the impact of past policies and avoid the repetition of previous failings.
pt. 1. Introduction to sustainable development indicators -- pt. 2. Sustainable development and national accounting -- pt. 3. Sustainable development and welfare -- pt. 4. Sustainable development and natural capital accounting -- pt. 5. Sustainable development and indicators of human-environment interaction -- pt. 6. Concluding assessments of sustainable development indicators.
Includes bibliographical references and index.
Keywords: Environmental economics; Sustainable development -- Statistics; Economic indicators; Electronic books